PENGARUH KUALITAS PELAYANAN, KEWAJIBAN MORAL, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK DAERAH - Lucia Rahmadika; Noor Shodiq Askandar; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACT  This research was conducted to determine the effect of service quality, moral obligation, and tax penalty on tax compliance when paying local taxes. In this study the researches took a sample of 75 respondents from hotel taxpayers who were registered at the Batu City Revenue Service. The analytical method used is multiple linear regression. Based on the test results it can be concluded that simultaneously variables of service quality, moral obligation, and tax penalty have a significant effect on the tax compliance. Partially the service quality variable does not have a significant effect on taxpayer compliance. While the variable moral obligations and tax penalty have a significant effect on taxpayer compliance. This research contribute to theory of planned behavior.Keywords        : Quality of service, moral obligations, tax sanctions, and taxpayer compliance.